Elementary students' perceptions of classroom resilience-promoting factors in China and the United States. Issue 1 (2nd January 2020) - Ni, Hong; Li, Chieh; Li, Beilei; Xi, Honghua
ABSTRACT: This study used ClassMaps Survey to investigate third to fifth grade elementary students' perceptions of five relational (e.g., teacher-student relationships and peer friendships) and three individual (e.g., academic self-efficacy and behavioral self-control) resilience-promoting factors in classrooms in China and the United States. Examination of measurement equivalence indicates that the seven-factor model excluding peer aggression has acceptable strong factorial measurement equivalence. Comparison of group means revealed common strengths in teacher–student relationships, peer friendships, challenges in behavioral self-control, and peer conflict across the two cultural groups. Interventions should be built upon positive relationships and target behavioral self-control and peer conflict.